Exhausting circ_0136474 and Restoring miR-766-3p Attenuate Chondrocyte Oxidative Injury in IL-1β-Induced Osteoarthritis Progression Through Regulating DNMT3A - Zhu, Haiquan; Zhu, Shaobo; Shang, Xiuchao; Meng, Xiangsheng; Jing, Sheng; Yu, Li; Deng, Yu (Frontiers in Genetics, 2021)
Circular RNA circ_0136474 is a new contributor of human osteoarthritis (OA) by suppressing chondrocyte proliferation. However, its role and mechanism in OA chondrocyte injury remain ill-defined. Herein, we performed real-time quantitative PCR to detect RNA expression of circ_0136474, microRNA (miR)-766-3p and DNA methyltransferase 3A (DNMT3A), and utilized western blotting to measure protein expression of DNMT3A, matrix metalloproteinase-1 (MMP1), MMP13, Collagen II, proliferating cell nuclear antigen (PCNA) and B cell lymphoma (Bcl)-2, and Bcl-2-associated X protein (Bax). Direct interaction between miR-766-3p and circ_0136474 or DNMT3A was confirmed by bioinformatics algorithms, dual-luciferase reporter assay and RNA immunoprecipitation. Functional experiments including cell counting kit-8 assay, flow cytometry and special assay kits were employed to measure oxidative injury in interleukin (IL)-1β-induced OA-like chondrocytes. Firstly, IL-1β administration induced cell viability inhibition, Collagen II suppression and promotion of MMP1 and MMP13 in human chondrocyte CHON-001 cells. Expression of circ_0136474 and DNMT3A was upregulated, and miR-766-3p was downregulated in human OA cartilages and IL-1β-induced CHON-001 cells. Functionally, both blocking circ_0136474 and upregulating miR-766-3p could rescue cell viability and levels of PCNA, Bcl-2, reduced glutathione (GSH) and total superoxide dismutase (SOD), and attenuate apoptosis rate and levels of Bax, reactive oxygen species (ROS) and lipid peroxidation malondialdehyde (MDA). Mechanically, circ_0136474 served as miR-766-3p sponge to govern miR-766-3p-targeted DNMT3A expression. Accidently, restoring DNMT3A counteracted miR-766-3p upregulation role and silencing miR-766-3p weakened circ_0136474 knockdown effect in IL-1β-induced CHON-001 cells. In conclusion, exhausting circ_0136474 could mitigate OA chondrocytes oxidative injury through regulating miR-766-3p/DNMT3A axis.